Cost-Effectiveness Analysis of Carboplatin-Paclitaxel, Cisplatin-Pemetrexed, and Carboplatin-Gemcitabine Chemotherapy Regimens in Patients with Non-Small Cell Lung Cancer at Persahabatan Central General Hospital - Melinda, Venni; Anggriani, Yusi; Khairani, Sondang; Nurhayati, Fitri (Sciences of Pharmacy, 2026)
Platinum-based chemotherapy remains an important treatment option for patients with advanced non-small cell lung cancer (NSCLC), particularly in settings where reimbursement and resource allocation are major considerations. A retrospective observational cost-effectiveness study was conducted using medical records and billing data from adult patients with NSCLC who received carboplatin–paclitaxel, cisplatin–pemetrexed, or carboplatin–gemcitabine in 2023. Effectiveness outcomes included the one-year survival rate (%) and median progression-free survival (PFS). Costs were calculated based on direct medical expenses over six chemotherapy cycles. Cost-effectiveness was assessed using ACER, ICER, and dominance analysis. A total of 101 patients were included: 81 received carboplatin and paclitaxel, 14 received cisplatin and pemetrexed, and 6 received carboplatin and gemcitabine. Mean direct medical costs were IDR 27,588,547, IDR 41,214,281, and IDR 47,471,752, respectively. No statistically significant differences were observed in one-year survival rate or median PFS among the regimens, although interpretation should consider the unequal sample sizes (81 vs. 14 vs. 6), which limit statistical power. Based on one-year survival, carboplatin–paclitaxel had the lowest ACER and dominated the other regimens by providing higher observed survival at lower cost. Based on median PFS, cisplatin–pemetrexed provided longer PFS than carboplatin–paclitaxel but at a higher cost, requiring ICER-based interpretation. Carboplatin–paclitaxel was associated with the lowest direct medical cost and the most favorable cost-effectiveness profile based on one-year survival among the evaluated regimens. However, conclusions should be interpreted cautiously because of the retrospective design, small and unequal group sizes, and potential confounding by baseline clinical characteristics.